High-Resolution Analysis of Gut Environment and Bacterial Microbiota Reveals Functional Compartmentation of the Gut in Wood-Feeding Higher Termites (Nasutitermes spp.) - Köhler, Tim (American Society for Microbiology, 2012)
Higher termites are characterized by a purely prokaryotic gut microbiota and an increased compartmentation of their intestinal tract. In soil-feeding species, each gut compartment has different physicochemical conditions and is colonized by a specific microbial community. Although considerable information has accumulated also for wood-feeding species of the genus Nasutitermes, including cellulase activities and metagenomic data, a comprehensive study linking physicochemical gut conditions with the structure of the microbial communities in the different gut compartments is lacking. In this study, we measured high-resolution profiles of H(2), O(2), pH, and redox potential in the gut of Nasutitermes corniger termites, determined the fermentation products accumulating in the individual gut compartments, and analyzed the bacterial communities in detail by pyrotag sequencing of the V3-V4 region of the 16S rRNA genes. The dilated hindgut paunch (P3 compartment) was the only anoxic gut region, showed the highest density of bacteria, and accumulated H(2) to high partial pressures (up to 12 kPa). Molecular hydrogen is apparently produced by a dense community of Spirochaetes and Fibrobacteres, which also dominate the gut of other Nasutitermes species. All other compartments, such as the alkaline P1 compartment (average pH, 10.0), showed high redox potentials and comprised small but distinct populations characteristic for each gut region. In the crop and the posterior hindgut compartments, the community was even more diverse than in the paunch. Similarities in the communities of the posterior hindgut and crop suggested that proctodeal trophallaxis or coprophagy also occurs in higher termites. The large sampling depths of pyrotag sequencing in combination with the determination of important physicochemical parameters allow cautious conclusions concerning the functions of particular bacterial lineages in the respective gut sections to be drawn.